Islamic Education in Modern Society: A Bibliometric Review of Literature - Judijanto, Loso (West Science Islamic Studies, 2025)
This study offers a thorough bibliometric analysis of Islamic education in contemporary culture, examining 324 papers indexed in Scopus and Web of Science from 2019 to 2024. The research employs VOSviewer and Biblioshiny to map keyword co-occurrence, author collaboration, and country networks, therefore elucidating the intellectual and geographical framework of the topic. The findings reveal five predominant themes: pedagogical modernization, multicultural education, gender discourse, digital integration, and Islamic ethics. The United States, United Kingdom, Malaysia, and Indonesia are identified as the primary donors and centers of collaboration. The findings indicate a distinct shift from theology-focused studies to interdisciplinary methodologies that incorporate technology, social inclusion, and educational reform. This study enhances understanding by illustrating worldwide research patterns and pinpointing new chances for collaboration and theoretical advancement.